Brain Gym Therapy: Focus Attention as an Effort to Improve Student Learning Concentration - Diah Rahayu; Muhammad Ali Adriansyah; Dian Dwi Nur Rahmah; Princess Yustisia Tri Sanhadi; Muhammad Qori Hasan; Moutiq Nur Kalbu (Universitas Pendidikan Ganesha, 2022)
Currently, all levels of education carry out the learning process online. They start from primary, secondary, to higher education. At the higher education level, students who usually do face-to-face learning activities face-to-face with other lecturers and students now must do the same activities virtually. This study aims to analyze whether there are differences in the concentration level in the study of students after being treated with brain gym therapy with the PACE movement. This study uses an experimental approach with a two-group pre and post-test design. The subjects of this study were 60 students divided into two groups, 30 in the experimental group and 30 in the control group, who met the research criteria. The data analysis technique used paired sample t-test. The results showed that there was a difference in learning concentration for students after being given PACE brain gym therapy with the results of the paired sample t-test with a value of = 0.042 (p less than 0.05). There is no difference in learning concentration for students after being given brain gym therapy material and learning concentration with the results of the paired sample t-test with a value of = 0.82 (p more than 0.05). Through this study, students' learning concentration can be improved by doing pace brain gym therapy movements. Increasing student concentration can be increased by doing brain gym therapy as a habit every time before doing learning activities that are expected to help increase student concentration.